The challenges of mobile banking application on novice users - Hussain, Azham; Thamer, Aysar; Matcharan, Adilah (IP Publishing LLC, 2018)
Banks procedures are one of the most monotonous and long activities, bank users would have to waste time to finish tasks that can be done online, although there is a website designed by Maybank but the use of smartphones are ever growing and led to developing the Maybank mobile application. Maybank mobile application is designed to mainly cater for users on the go, but as many emerging technologies adopted by developing enterprises, the usability of the application should be measured to assess user’s overall satisfaction with the application. A study conducted in UUM Sintok with 15 participants, they were given four tasks to perform and were given questionnaires to elicit their experience. The findings of this study revealed that participants were generally pleased with the functions provided in the application.